Upstream ORFs Influence Translation Efficiency in the Parasite Trypanosoma cruzi - Radío, Santiago; Garat, Beatriz; Sotelo-Silveira, José; Smircich, Pablo (Frontiers in Genetics, 2020)
It is generally accepted that the presence of ORFs in the 5’ untranslated region of eukaryotic transcripts modulates the production of proteins by controlling the translation initiation rate of the main CDS. In trypanosomatid parasites, which almost exclusively depend on post-transcriptional mechanisms to regulate gene expression, translation has been identified as a key step. However, the mechanisms of control of translation are not fully understood. In the present work, we have annotated the 5’UTRs of the Trypanosoma cruzi genome both in epimastigotes and metacyclic trypomastigotes and, using a stringent classification approach, we identified putative regulatory uORFs in about 9% of the analyzed 5’UTRs. The translation efficiency (TE) and translational levels of transcripts containing putative repressive uORFs were found to be significantly reduced. These findings are supported by the fact that proteomic methods only identify a low number of proteins coded by transcripts containing repressive uORF. We additionally show that AUG is the main translation initiator codon of repressive uORFs in T. cruzi. Interestingly, the decrease in TE is more pronounced when the uORFs overlaps the main CDS. In conclusion, we show that the presence of the uORF and features such as initiation codon and/or location of the uORFs may be acting to fine tune translation levels in these parasites.